Analysis of Inhibitory Effect of the Double-layer Nano-infusion on Vascular Restenosis in Animal Models of Coronary Atherosclerosis: Effect of Double-layer Nano-infusion on Vascular Restenosis - Cao, Ge; Kang, Hui; Yu, Hui; He, Qing (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effect of double-layer nano-infusion on restenosis in animal models of coronary atherosclerosis (CAD). For this purpose, forty Apolipoprotein E (APOE) gene mice (ApoE -/ -) were fed with 1.25% cholesterol, 10% fat, and 88.75% standard diet to establish CAD models. They were classified into the control group with paclitaxel nanoparticles (PTX-NPs) and the observation group with balloon infusion of PTX combined with vascular endothelial growth factor (VEGF) double-layer nanoparticles (V-P-NPs). The vascular endothelial healing and the occurrence of vascular restenosis were assessed. Results showed no significant differences in the particle size, distribution, and Zeta-potential between PTX-NPs and V-P-NPs (P>0.05). According to the transmission electron microscope (TEM), the nanoparticles had good dispersity, and the structure of the inner and outer layers of V-P-NPs was obvious. There were insignificant differences between the entrapment efficiency of PTX in PTX-PNS and the PTX and VEGF in V-P-NPs (94.32%, 95.66%, 97.89%) and drug-loading rate (28.91%, 30.12%, 29.91%) (P>0.05). The vascular endothelial healing degree of the observation group was better than that of the control group under optical coherence tomography (OCT). The restenosis, including the stenosis (6.91±7.59)%, proliferation (0.12±0.02), and the maximum intima thickness (0.07±0.09)mm of the observation group was decreased compared with the control group ((24.01±12.78)%, (0.28±0.01), (0.19±0.08)mm) (P<0.05). Then the double-layer nano-infusion therapy was conducive to healing vascular endothelial tissue and could effectively inhibit vascular restenosis, with clinical adoption value.